The Relationship between Gene Expression of Human Leukocyte Antigen – DR4 and Enteric Bacteria as Environmental Factor in Iraqi Patients with Rheumatoid Arthritis - Gahli, Estabraq D.; Mohammd, Haethem Q. (Iraqi Journal of Science, 2025)
Rheumatoid arthritis (RA) is a complex autoimmune disorder that is shaped by the interplay of genetic predisposition and environmental triggers, which collectively contribute to the onset and progression of the disease. This study pursued three key goals: first, to estimate the expression levels of the Human Leukocyte Antigen – DR4 )HLA DR4 (gene; second, to identify the predominant enteric bacteria in rheumatoid arthritis (RA) patients and healthy controls; and third, to examine the association between HLA-DR4 gene expression and the identified bacterial profiles. The case-control study involved 100 blood specimens and 100 stool specimens were collected from 50 RA patients and 50 healthy individuals. RNA was extracted and cDNA was synthesized, then by RT -PCR was used to detect HLA DR4gene expression. Also, Stool specimens were collected and analyzed using culturing, biochemical tests, antibiotic sensitivity tests, and 16S rRNA PCR. This process helped evaluate the distribution of enteric bacteria and detect the bacterial Cefotaximase-M (CTXM) gene. The results indicated that HLA DR4 gene expression was highly expressed in RA patients compared with the control. Escherichia coli is the predominant enteric bacteria in the stools of patients, and they carry the highest level of the CTXM antibiotic resistance gene, other enteric bacteria were diagnosed also; which included Staph aureus, Shigella sonnei, Klebsiella pneumonia, Proteus marbilus, and Pseudomonas aeruginosa while Controls enteric bacteria include E.coli, Lactobacillus spp., Enterococcus spp., and Bifidobacterium spp., among the total sample, there was no significant difference in mean between HLA DR4 gene expression and the bacterial distribution. The present study indicates that the HLA DR4 gene and enteric microbial dysbiosis are involved in RA pathogenesis. These elements are expected to be crucial in identifying potential biomarkers and predictors that can aid in the diagnosis of the condition.